Statement by the Managing Director on the Independent Evaluation Office Report on Growth and Adjustment in IMF-Supported Programs. - International Monetary Fund. Independent Evaluation Office (Washington, D.C. : International Monetary Fund, 2021)
Statement by the Managing Director on the Independent Evaluation Office Report on Growth and Adjustment in IMF-Supported Programs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fiscal Policy; Monetary Policy; Political Economy